2013
DOI: 10.1002/adma.201300595
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Substituted Magnetite Nanoparticles and Their Assembly into Ferrimagnetic Nanoparticle Arrays

Abstract: A simple process to prepare monodisperse ferrimagnetic cobalt-substituted magnetite Co(x)Fe(3-x)O4 nanoparticles is reported. These ferrimagnetic nanoparticles are readily dispersed in hexane, forming a stable ferrimagnetic nanoparticle dispersion, and allowing easy nanoparticle self-assembly. When assembled under an external magnetic field (5.5 kOe), these nanoparticles show preferred magnetic alignment with their H(c) reaching 2.49 kOe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 31 publications
10
86
0
Order By: Relevance
“…When polyhedral NPs react with TOP( Supporting Information, Figure S3 A-E), some rods are formed after only 1.5 ho f reaction. Also,i ns ome NPs,i ti sp ossible to see how "rodlike" protuberances emerge from their surface,indicating the growth of M-P from the M-O surface.I mages after 3, 6, and 12 hofreaction show the progressive formation/elongation of the rods as ac onsequence of the phosphidation of all of the oxide NPs.T he exposed planes on these single-crystal structures (generally (311) or (111)) [8] are readily available for Pdiffusion, and therefore growth along asingle direction is observed. On the other hand, when the nanocubes are used as seeds (Supporting Information, Figure S3 F-J), it can be seen that after 1.5 ho fr eaction the cubes initially adopt concave shapes that later grow into the sea-urchin structures.…”
Section: Methodsmentioning
confidence: 99%
“…When polyhedral NPs react with TOP( Supporting Information, Figure S3 A-E), some rods are formed after only 1.5 ho f reaction. Also,i ns ome NPs,i ti sp ossible to see how "rodlike" protuberances emerge from their surface,indicating the growth of M-P from the M-O surface.I mages after 3, 6, and 12 hofreaction show the progressive formation/elongation of the rods as ac onsequence of the phosphidation of all of the oxide NPs.T he exposed planes on these single-crystal structures (generally (311) or (111)) [8] are readily available for Pdiffusion, and therefore growth along asingle direction is observed. On the other hand, when the nanocubes are used as seeds (Supporting Information, Figure S3 F-J), it can be seen that after 1.5 ho fr eaction the cubes initially adopt concave shapes that later grow into the sea-urchin structures.…”
Section: Methodsmentioning
confidence: 99%
“…59,60 Similar theoretical and experimental investigations on bulk Co x Fe 3−x O 4 also reveal that the coercivity of the cobalt ferrite increases with x from 0 to 0.7 but decreases when x is beyond 0.7, which is validated in the Co x Fe 3−x O 4 NPs. 61,62 3. SYNTHESIS OF MAGNETIC NANOPARTICLES As the properties of magnetic NPs are strongly dependent on their dimensions, compositions, and structures, extensive efforts have been made to synthesize these NPs with fine controls over the size, shape, composition, and structure.…”
Section: Composition Effectmentioning
confidence: 99%
“…Therefore, continuing efforts have been devoted to the synthesis of new MNPs with improved magnetic properties [7][8][9][10][11] . Interestingly, Doaga et al 9 have reported that relative to Fe3O4 nanoparticles, manganese-doped iron oxide nanoparticles of MnxFe1-xFe2O4 (0 ≤ x ≤ 1) show the enhanced saturation magnetization (Ms) and hence the enhanced specific absorption rate (SAR), which is a measure of heating efficiency.…”
Section: Introductionmentioning
confidence: 99%